1989
DOI: 10.1099/0022-1317-70-10-2573
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot Analysis of the Antibody Response to Murine Cytomegalovirus in Genetically Resistant and Susceptible Mice

Abstract: SUMMARYThe murine model of human cytomegalovirus infection was employed to analyse the kinetics of antibody production to murine cytomegalovirus (MCMV) structural and immediate early (IE) polypeptides following MCMV infection of genetically resistant and susceptible strains of mice. A total of 22 structural and six non-structural, IE proteins were identified. Analysis of immunoblots by densitometry identified four patterns of antibody reactivity to MCMV structural polypeptides during primary and secondary anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Origins of wild-derived isolates (G1F, G3F, G4, G5, G6, K6, K7, K17E, N1, N5, W3, W8211, MI6A) have been previously described (20,31). Tissue culture virus stocks were produced by propagation in MEFs or M210B4 cells and titers determined by standard plaque assay as previously described (32). Virulent salivary gland viral (SGV) stocks were prepared by infecting 3-wk-old female BALB/c mice i.p.…”
Section: Virus Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Origins of wild-derived isolates (G1F, G3F, G4, G5, G6, K6, K7, K17E, N1, N5, W3, W8211, MI6A) have been previously described (20,31). Tissue culture virus stocks were produced by propagation in MEFs or M210B4 cells and titers determined by standard plaque assay as previously described (32). Virulent salivary gland viral (SGV) stocks were prepared by infecting 3-wk-old female BALB/c mice i.p.…”
Section: Virus Stocksmentioning
confidence: 99%
“…Expression of m157 from the vARK25-m157 G1F and vARK25-m157 K181-revertant viruses was confirmed using infected M210B4 cells in a reporter assay (data not shown). The recombinant viruses (vARK25-m157 G1F , vARK25-m157 C2-mutant , and vARK25-m157 K181-revertant ) and parental K181 virus (derived from pARK25) were used to infect adult B6 mice at the dose of 1 3 10 4 PFU/mouse, and viral titers in the target organs (spleen, liver, lungs, and salivary glands) were compared by standard plaque assay as described (32).…”
Section: Construction Of M157 Gene-swap Mcmvs and Analysis Of In Vivomentioning
confidence: 99%
“…The MCMV strains used in this study included the laboratory strain K181, and the MCMV field isolates G1A, G2, G3A, G3B, G3E, (34, G5, W2, W3, W4, W5, W7, W8, WE6, W8211, W9077, K4, K6, K7, K10, K17A, K17B, K17E, K29 and N1 (Booth et al, 1993). The MCMV strains were propagated in mouse embryo fibroblasts (MEF) by standard procedures (Farrell & Shellam, 1989). The K181 strain was also maintained by serial passage in the salivary glands of mice as described previously (Allan & Shellam, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal antibody responses to multiple viral proteins occur following MCMV infection, with production of virus specific antibodies of both IgG and IgM classes (Araullo-Cruz et al, 1978;Farrell and Shellam, 1989;Karupiah et al, 1998;Lawson et al, 1988;Selgrade et al, 1983). Adoptive transfer of anti-CMV antibody has been shown to be protective during acute infection (Araullo-Cruz et al, 1978;Farrell and Shellam, 1991;Lawson et al, 1988;Shanley et al, 1981), but does not prevent development of latent infection (Shanley et al, 1981).…”
Section: Humoral Responses Have Been Fairly Well Characterized Bmentioning
confidence: 99%
“…Numerous techniques have been described that detect MCMV-specific antibody responses in mouse sera following infection with MCMV. These include nuclear anti-complement immunofluorescence, viral immunoblotting, complement fixation, indirect immunofluorescence, indirect hemagglutination, and enzyme-liked immunosorbent assay (ELISA) techniques (Anderson et al, 1983;Anderson et al, 1986;Castellano et al, 1977;Classen et al, 1987;Farrell and Shellam, 1989;Kettering et al, 1977;Lussier et al, 1987;Selgrade et al, 1983). We have found that use of these techniques, which each have their specific strengths and weaknesses, can be time consuming and tedious.…”
Section: Introductionmentioning
confidence: 99%